Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Loyalitas Dengan Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Kasus Pada Pelanggan Rei Adventure Store Dinoyo) - Endang Isiyowati; Agus Widarko; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to directly analyze product quality on customer loyalty, directly analyze service quality on customer loyalty, directly analyze customer satisfaction with customer loyalty and indirectly analyze product quality and service quality on loyalty with satisfaction as an intervening variable to consumers Rei Adventure Store. This study uses a quantitative approach.Rei Adventure Store Dinoyo 5 months ago 450 research samples in this study were 82 consumers.With a purposive sampling technique sampling. Data analysis using Path analysis.by conducting an instrument test, a reliability test, a normality test, a hypothesis test, and a sobel test. The results showed that there was a significant difference between quality and service quality on satisfaction. There is a significant difference in service quality on loyalty. While product quality is considered insignificant on loyalty. Is a significant influence on satisfaction with loyalty. Satisfaction is not able to memdiasi influence of product quality and service quality on loyalty. Keywords: Product quality, service quality, satisfaction and loyalty